REVIEWS (Heythrop journal, 1974)
Books Reviewed in this Article: Benito Arias Montano (1572-1598) By B. Rekers. Pp. xi, 199 (Studies of the Warburg Institute 33), London, Warburg Institute; Leiden, E. J. Brill, 1972, £5.00 Edmund of Abingdon's ‘Speculum Religiosorum’ and ‘Speculum Ecclesie’. Edited by Helen P. Forshaw. Pp. vii, 125 (Auctores Britannici Medii Aevi 3), London Oxford University Press, 1973, £5.00. English Schools in the Middle Ages. By Nicholas Orme. Pp. xiv, 370, London, Methuen, 1973, £7.25. Heresy and Obedience in Tridentine Italy: Cardinal Pole and the Counter-Reformation. By Dermot Fenlon. Pp. xiii, 300, Cambridge, Cambridge University Press, 1972, £5.80. The Churches Militant: The War of 1812 and American Religion. By William Gribbin. Pp. viii, 210, New Haven and London, Yale University Press, 1973, £3.75. English Roman Catholics and Higher Education 1830-1903. By Vincent Alan McClelland. Pp. x, 453, Oxford, Clarendon Press, 1973, £7.00. Lord Acton on Papal Power. By H. A. MacDougall. Pp. ix, 241, London, Sheed & Ward, 1973, £4.00. The English Bishops and the First Vatican Council., By Frederick J. Cwiekowski. Pp. xxvii, 341, (Bibliothèque de la Revue d'Histoire Ecclésiastique 52) Louvain, Publications Universitaires de Louvain, 1971, 500 Belg. Frs. Genesis 1-11. By R. Davidson. Pp. x, 118, Cambridge, Cambridge University Press, 1973, £1.90. The Book of the Prophet Isaiah, 1-39. By A. S. Herbert. Pp. xiii, 219, Cambridge, Cambridge University Press, 1973, £3.50. The First and Second Books of the Maccabees. By John R. Bartlett. Pp. xiv, 358, Cambridge, Cambridge University Press, 1973, £5.20. Deuteronomy. By A. Phillips. Pp. xiv, 237, Cambridge, Cambridge University Press, 1973, £3.80 (hardback), £1.50 (paperback). The Wisdom of Solomon. By E. G. Clarke Pp. xii, 136, Cambridge, Cambridge University Press, 1973, £2.20 (hardback), £1.10 (paperback). I and II chronicles, Ezra, Nehemiah. By P. R. Ackroyd. Pp. 320 (Torch Bible Commentaries), London, SCM Press, 1973, £1.40. La Verdad Os Hará Libres: Jn 8, 32. By José O. Tunñi Vancells. Pp. 230, Barcelona, Herder, 1973, no price given. Martyria. Traditionsgeschichtliche Untersuchungen zum Zeugnisthema bei Johannes. By Johannes Beutler, S. J. Pp. 398 (Frankfurter theologische Studien 10), Frankfurt, Josef Knecht, 1972, 48 DM. The Use of the Old Testament in the New and Other Essays. Edited by James M. Efird. Pp. xv, 332, Durham, N. C., Duke University Press, 1972, $14.75. Pre-Existence, Wisdom and the Son of Man: A Study of the Idea of Pre-Existence in the New Testament. By R. G. Hamerton-Kelly. Pp. xii, 310, Cambridge, Cambridge University Press, 1973, £7.90. The Easter Jesus. By Gerald O'Collins. Pp. xiv, 142, London, Darton, Longman And Todd, 1973, £1.50. Four Martyrdoms from the Pierpoint Morgan Coptic Codices. Edited by E. A. E. Reymond and J. W. Barns. Pp. xii, 278, Oxford, Clarendon Press, 1973, £7.50. Studies in the History of Philosophy and Religion. Volume I. By Harry Austryn Wolfson, edited by Isadore Twersky and George H. Williams. Pp. xvii, 626, Cambridge (Mass.), Harvard University Press, 1973, £8.00. Complete Prose Works of John Milton, Volume 6: Christian Doctorine. Edited with an introduction by Maurice Kelley, translated by John Carey. Pp. xxiv, 863 Haven and London, Yale University Press, 1973, £10.50. Gerard Manley Hopkins and the Victorian Temper. By Alison G. Sulloway. Pp. xiv, 245, London, Routledge and Kegan Paul, 1972, £3.75. Kierkegaard: A Biographical Introduction. By Ronald Grimsley. Pp. 127 (Leaders of Modern Thought), London, Studio Vista, 1973, £0.95. Ludwig Wittgenstein: Letters to C. K. Ogden. Edited by G. H. von Wright. Pp. ix, 90, Oxford, Basil Blackwell, and London, Routledge and Kegan Paul, 1973, £2.00. The Central Questions of Philosophy. By A. J. Ayer. Pp. 243, London, Nicolson, 1973, £3.50. Elements of Analytic Philosophy. By Arthur Pap. Pp. xvi, 542, New York, Hafner Publishing Company, 1972, £6.20. An Introduction to Confirmation Theory. By Richard Swinburne. Pp. 218, London, Methuen, 1973, £3.90. Models for Divine Activity. By Ian T. Ramsey. Pp. 78, London, SCM Press, 1973, £1.95. Ian Ramsey, Bishop of Durham—a Memoir. By David L. Edwards. Pp. 101, London, Oxford University Press, 1973, £2.00. Change in Focus: A Study of Doctorinal Change and Continuity. By Nicholas Lash. Pp. ix, 198 (Library of Contemporary Theology), London, Sheed and Ward, 1973, £3.00. Basic Questions in Theology (Volume Three). By Wolfhart Pannenberg. Pp. ix, 213, London, SCM Press, 1973, £3.75. Wolfhart Pannenberg. By Allan D. Galloway. Pp. 143 (Contemporary Religious Thinkers Series), London, George Allen and Unwin, 1973, £3.25. Das Wesen Des Christentums. Eine bergriffsgeschichtliche Untersuchung. By Hans Wagenhammer. Pp. 262 (Tübinger theologische Studien 2), Mainz, Matthias Grünewald Verlag, 1973, 38 DM. The Oxford Dictionary of the Christian Church. Edited by F. L. Cross, second edition by F. L. Cross and E. A. Livingstone. Pp. xxxi, 1518, London, Oxford University Press, 1974, £13.50.